Modulated Start-Up Mode of Cancer Cell Migration Through Spinophilin-Tubular Networks - Hwang, Soyoung; Lee, Peter Chang-Whan; Shin, Dong Min; Hong, Jeong Hee (Frontiers in Cell and Developmental Biology, 2021)
Spinophilin is a multifunctional actin-binding scaffolding protein. Although increased research on spinophilin in cancer biology has revealed a tumor suppressive role, its modulation in cancer biology, and oncological relevance remains elusive. Thus, we determined the role of spinophilin in the modulation of the junctional network and cellular migration in A549 lung cancer cell line. Knockdown of spinophilin promoted cancer cell invasion in agarose spot and scratch wound assays. Attenuation of spinophilin expression also enhanced invadopodia, as revealed by enhanced vinculin spots, and enhanced sodium bicarbonate cotransporter NBC activity without enhancing membranous expression of NBCn1. Disruption of the tubular structure with nocodazole treatment revealed enhanced spinophilin expression and reduced NBC activity and A549 migration. Spinophilin-mediated junctional modulation and tubular stability affected bicarbonate transporter activity in A549 cells. The junctional modulatory function of spinophilin in start-up migration, such as remodeling of tight junctions, enhanced invadopodia, and increased NBC activity, revealed here would support fundamental research and the development of an initial target against lung cancer cell migration.